Exploring the economic consequences of letting a supplier hold reserve storage. (January 2015) - Abginehchi, Soheil; Larsen, Christian; Thorstenson, Anders
Abstract: We consider a single-item, periodic review inventory control problem with discrete non-stationary stochastic demand. The time horizon is finite and all shortages at the downstream level are backordered. There are two modes of supply: a normal supplier and a reserve storage supply. The reserve storage is capacitated and the downstream buyer can only order the entire inventory in the reserve storage or nothing. If the reserve storage is empty, it takes a fixed time interval before it is replenished again. Provided that the reserve storage is fully replenished it can be used at any time period, whereas orders to the normal supplier can only be issued at specific time periods. The lead time from the reserve storage is shorter than from the normal supplier, but using the reserve storage is more expensive than using the normal supplier. We use stochastic dynamic programming to specify an exact model of the problem. We also develop an approximate model which is computationally faster than the first model. The models are then used to analyze numerically the sensitivity with respect to key parameters like the reserve storage size and unit purchase cost. This paper is motivated by a problem presented during contacts with a leading Danish provider of communications solutions.